2013
DOI: 10.1158/1055-9965.epi-12-0658
|View full text |Cite
|
Sign up to set email alerts
|

Combination Aspirin and/or Calcium Chemoprevention with Colonoscopy in Colorectal Cancer Prevention: Cost-effectiveness Analyses

Abstract: Background: Clinical and cohort studies have shown that low-dose aspirin and calcium are effective lowrisk strategies for primary prevention of colorectal cancer (CRC). We compared the cost-effectiveness of aspirin and calcium chemoprevention used with colonoscopy for primary prevention of CRCs.Methods: Markov chain Monte Carlo simulations for a population of 100,000 persons, with a colonoscopy compliance rate of 50%, were used for the analysis. If adenomas were detected, colonoscopy was repeated every 4 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…A less common strategy (n ¼ 1 of 27 [4%]) included transitions between CRC stages while assuming that each CRC stage has a without-screening state or a screen-detected state with different survival rates [38]. Few studies (n ¼ 4 of 27 [15%]) modeled CRC progression between stages, but insufficient information is provided regarding sojourn time and lead time because only diagnosed CRC states are modeled [34][35][36][37].…”
Section: General Characteristics and Modeling Strategiesmentioning
confidence: 99%
“…A less common strategy (n ¼ 1 of 27 [4%]) included transitions between CRC stages while assuming that each CRC stage has a without-screening state or a screen-detected state with different survival rates [38]. Few studies (n ¼ 4 of 27 [15%]) modeled CRC progression between stages, but insufficient information is provided regarding sojourn time and lead time because only diagnosed CRC states are modeled [34][35][36][37].…”
Section: General Characteristics and Modeling Strategiesmentioning
confidence: 99%
“…In the present review we observed that although most articles (n = 19; 58%) adequately reported study perspective, approximately 30% (n = 10) of them failed to relate it to the costs being evaluated [25,27,28,30,31,37,39,42,45,46]. Conversely, 12% (n = 4) of the studies did not report it [33,35,40,47].…”
Section: Resultsmentioning
confidence: 66%
“…Most of the studies used a health care payer (n = 14; 42,4%) [21,2331,41,42,44,52] or a third-party payer perspective (n = 14; 42,4%) [20,22,34,3639,43,45,46,4851]; perspective was not reported in four studies (12,1%)[33,35,40,47]; while only one study used a societal perspective (3%)[33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A population-based study by De Monte et al [104] showed improved survival for type II diabetes patients with stage II and III CRC with aspirin and metformin. Several researchers have been explored combination of aspirin and calcium as one of the cost effective and low-risk strategies with colonoscopy for primary prevention of CRC [105]. …”
Section: Selected Anti-inflammatory Agents For Colon Cancer Prevenmentioning
confidence: 99%